Armoring LiNi1/3Co1/3Mn1/3O2 Cathode with Reliable Fluorinated Organic–Inorganic Hybrid Interphase Layer toward Durable High Rate Battery. (13th March 2020) - Chen, Yu; Zhao, Weimin; Zhang, Quanhai; Yang, Guangzhi; Zheng, Jianming; Tang, Wei; Xu, Qunjie; Lai, Chunyan; Yang, Junhe; Peng, Chengxin
Abstract: Ternary layered oxide materials have attracted extensive attention as a promising cathode candidate for high‐energy‐density lithium‐ion batteries. However, the undesirable electrochemical degradation at the electrode–electrolyte interface definitively shortens the battery service life. An effective and viable approach is proposed for improving the cycling stability of the LiNi1/3 Co1/3 Mn1/3 O2 cathode using lithium difluorophosphate (LiPO2 F2 ) paired with fuoroethylene carbonate (FEC) as co‐additives into conventional electrolytes. It is found that the co‐additives can greatly reduce the interface charge transfer impedance and significantly extend the life span of LiNi1/3 Co1/3 Mn1/3 O2 //Li (NMC//Li) batteries. The developed cathode demonstrates exceptional capacity retention of 88.7% and remains structural integrity at a high current of 5C after 500 cycles. Fundamental mechanism study indicates a dense, stable fluorinated organic–inorganic hybrid cathode‐electrolyte interphase (CEI) film derived from LiPO2 F2 in conjunction with FEC additives on the surface of NMC cathode material, which significantly suppresses the decomposition of electrolyte and mitigates the dissolution of transition metal ions. The interfacial engineering of the electrode materials stabilized by the additives manipulation provides valuable guidance for the development of advanced cathode materials. Abstract : An effective strategy for improving the cycling stability of the LiNi1/3 Co1/3 Mn1/3 O2 (NMC) cathode by in situ constructing a reliable fluorinated organic–inorganic cathode–electrolyte interphase film with lithium difluorophosphate combining fuoroethylene carbonate as coadditives is presented. Electrochemical tests demonstrate that the NMC cathode delivers 114 mAh g −1 with an exceptional capacity retention of 88.7% after 500 cycles even at a high rate of 5C.